Efeito antinociceptivo da mistura de triterpenos pentacíclicos alpha- e beta- amirina em modelos de nocicepção visceral em camundongos. - Lima Júnior, Roberto César Pereira (2005)
Protium heptaphyllum March (Burseraceae), a medicinal plant commonly found in the Amazon and in the Northeast regions of Brazil, releases an oil-resin rich in pentacyclic triterpenes, such as the binary mixture of alpha- and beta- amyrin, that manifests antiinflamatory, antinociceptive and gastroprotective properties. This work was aimed to evaluate the antinociceptive effect of the alpha- and beta- amyrin mixture in the cyclophosphamide (400 mg/kg), acetic acid (0,6%, 10mL/kg, i.p.) and mustard oil-induced visceral nociception models in mice and to establish the likely mechanism(s) of action. In the cyclophosphamide-induced visceral pain model, pretreatment of mice with triterpene mixture at the oral doses of 10, 30 and 100 mg/kg significantly reduced (p<0.001) the pain-related behavioral expression time (59,7; 75,5 e 92,3%, respectively, versus the cyclophosphamide-treated group 12,25 +/- 2,98 min) in a dose-dependent manner. Suppression of visceral pain–related behaviors was also evidenced to the triterpenoid mixture (10 mg/kg) in the intraperitoneal acetic acid- and intracolonically injected mustard oil-induced test models of visceral nociception 50,4% e 61,1%, respectively compared to the acetic acid-treated group (42,33 +/- 3,78 abdominal constrictions/20 min) in the writhing test and to the control in the mustard oil (0,75%, 50 mcL/animal) experiment (39,28 +/- 3,26). In these tests, the maximal suppression of visceral pain was observed at 10 mg/kg. The possible mechanisms involved in the antinociceptive action of alpha- and beta- amyrin (10 mg/kg) were analyzed in the mustard oil-induced visceral pain model. In the evaluation of the opioid receptor involvement, both the triterpene mixture and morphine (5 mg/kg, s.c.) effectively inhibited (p<0.001) the number of pain-related behaviors, which could be significantly reversed by pretreatment of animals with an opioid antagonist naloxona (2mg/kg, i.p.), suggesting the opioid participation in the alpha- and beta- amyrin mechanism of action. In the study of the alpha2-adrenoreceptor involvement, the triterpene mixture as well as clonidine (0.1 mg/kg, i.p.), a known alpha2 agonist, inhibited (p<0.001) the nociceptive behavioral expression. However, when the animals were pretreated with yohimbine, an alpha2-adrenoreceptor antagonist, only the inhibitory action of clonidine was reversed, suggesting the non-participation of alpha2- adrenoreceptor in the antinociceptive action of alpha- and beta- amyrin. In the evaluation of TRPV1 receptor involvement, mice pretreated with either the alpha- and beta- amyrin, ruthenium red, a TRPV1 non-competitive antagonist, (3 mg/kg, s.c.) or their combination induced a significant and similar inhibition (p<0.001) of the number of nociceptive behaviors. The degree of inhibition with no potentiation or antagonism suggests that alpha- and beta- amyrin may act as a TRPV1 non-competitive antagonist, like ruthenium red. In order to evaluate a possible sedative, motor impairment and motor incoordination effects related to alpha- and beta- amyrin, the penthobarbitone-induced sleeping time, open-field and rota-rod tests were performanced, respectively. The data indicated that the treatment of animals with the alpha- and beta- amyrin mixture (10 mg/kg) was unable to cause sedation, motor impairment or motor incoordination effects (p>0.05), being even able to reverse (p<0.05) a mustard oil-induced motor impairment in the open field test. The results taken together strongly suggest the therapeutic potential of alpha- and beta- amyrin in oblitering visceral nociception through the mechanisms that involve the opioids and TRPV1 receptors.